Klotho gene polymorphism as a susceptibility factor for oxidative DNA damage in coronary artery disease - KARSLI, SEHER; YURDUN, TÜRKAN (My University, 2023)
The Klotho protein has been linked to the promotion of cardiovascular health maintenance through its capacity to enhance resistance against oxidative stress, thereby exerting protective effects. The potential involvement of Klotho gene polymorphisms in the regulation of human aging and age-related disorders, including coronary artery disease, chronic renal disease, osteoporosis, and stroke, is under investigation. The objective of our research was to investigate the association between the rs9527025 (Cys370Ser) polymorphism of the Klotho gene and coronary artery calcification, as well as the potential link between the rs9527025 polymorphism and oxidative DNA damage. The study involved a sample of 90 patients who had undergone coronary angiography. The genotyping of Cys370Ser in exon 2 of the Klotho gene was performed using the polymerase chain reaction. The evaluation of oxidative DNA damage was conducted using the alkaline comet test. The findings of the study revealed that there was no statistically significant association between the distribution of alleles in the Klotho SNPs and the occurrence of coronary artery disorders. In the meantime, the total comet score frequency was significantly associated with the rs9527025 polymorphism. The results of our study indicate that Klotho gene variants, particularly the C370S polymorphism (rs9527025), might play a role in influencing oxidative DNA damage in age-related diseases, such as coronary artery disease. In consequence, larger studies are required to confirm the association between Klotho deficiency and the progression of cardiovascular disease in order to elucidate risk factors for coronary artery disease and develop potential therapeutic strategies.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Cardiovascular disease; coronary artery disease; genetic polymorphism; Klotho; oxidative DNA damage; Cardiovascular disease; coronary artery disease; genetic polymorphism; Klotho; oxidative DNA damage.